138k views
2 votes
Convert the basis v1 = (-1,1,0)^T, V2 = (2,-1, 1)^T, V3 = (0, -1, 1)^T for Rinto an orthonormal basis, using the Gram Schmidt process and the standard inner product in R?

User FakeMake
by
5.2k points

1 Answer

5 votes

Answer:


{\bf e}_(1)=((-1,1,0))/(\lVert (-1,1,0) \rVert)=\left((-1)/(√(2)),(1)/(√(2)),0\right)


{\bf e}_(2)=\frac{{\bf v}_(2)-({\bf v}_(2)\cdot {\bf e}_(1)) {\bf e}_(1)}{\lVert {\bf v}_(2)-({\bf v}_(2)\cdot {\bf e}_(1)) {\bf e}_(1) \rVert}=\left((1)/(√(6)),(1)/(√(6)),\sqrt{(2)/(3)}\right)


{\bf e}_(3)=\frac{{\bf v}_(3)-({\bf v}_(3)\cdot{\bf e_(1)}){\bf e}_(1)-({\bf v}_(3)\cdot {\bf e}_(2)){\bf e}_(2)}{\lVert {\bf v}_(3)-({\bf v}_(3)\cdot{\bf e_(1)}){\bf e}_(1)-({\bf v}_(3)\cdot {\bf e}_(2)){\bf e}_(2) \rVert}=\left(-(1)/(√(3)),-(1)/(√(3)),(1)/(√(3))\right)

Explanation:

We have the basis of
\mathbb{R}^(3)
{\cal B}=\{(-1,1,0),(2,-1,1),(0,-1,1)\}. From this basis we want to determine another orthonormal basis
{\cal B}'=\{{\bf e}_(1),{\bf e}_(2),{\bf e}_(3)\} of
\mathbb{R}^(3).

The first step is to define
{\bf e}_(1) as:


{\bf e}_(1)=((-1,1,0))/(\lVert (-1,1,0) \rVert)=\left((-1)/(√(2)),(1)/(√(2)),0\right)

Now define
{\bf e}_(2) by:


{\bf e}_(2)=\frac{{\bf v}_(2)-({\bf v}_(2)\cdot {\bf e}_(1)) {\bf e}_(1)}{\lVert {\bf v}_(2)-({\bf v}_(2)\cdot {\bf e}_(1)) {\bf e}_(1) \rVert}=\left((1)/(√(6)),(1)/(√(6)),\sqrt{(2)/(3)}\right)

Now define
{\bf e}_(3) by :


{\bf e}_(3)=\frac{{\bf v}_(3)-({\bf v}_(3)\cdot{\bf e_(1)}){\bf e}_(1)-({\bf v}_(3)\cdot {\bf e}_(2)){\bf e}_(2)}{\lVert {\bf v}_(3)-({\bf v}_(3)\cdot{\bf e_(1)}){\bf e}_(1)-({\bf v}_(3)\cdot {\bf e}_(2)){\bf e}_(2) \rVert}=\left(-(1)/(√(3)),-(1)/(√(3)),(1)/(√(3))\right)

User Emma
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.